CTAB-assisted precipitation synthesis of Ca(OH)2 sorbent for CO2 captures - Mohd Daud, Farah Diana; Sreekantan, Srimala; Mohamed, Abdul Rahman (Trans Tech Publications, 2016)
Ca(OH)2 sorbent with novel pods bundle structure were successfully synthesized by precipitation method by using Cetyltrimethylammonium bromide (CTAB) as cationic surfactant. The effects of CTAB on the morphologies of Ca(OH)2 sorbent were investigated. The results showed that the presence of CTAB could significantly differ the shape and particle size of the Ca(OH)2 sorbent which synthesized in ethanol media at 35n°C for 30 minutes. The XRD pattern indicated that the as-prepared product were well-crystallized hexagonal phase of Ca(OH)2 sorbent. Possible mechanisms for the CTAB assisted particle growth of Ca(OH)2 sorbent was discussed. The Ca(OH)2 sorbent have been studied by thermal gravimetric analyzer (TGA) at a 650 ºC carbonation temperature. The morphological changes and particle size of the sorbent have greatly influenced the CO2 capture performance.